2023
DOI: 10.3389/fpsyt.2023.1253088
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and cognitive function in bipolar disorder patients with different onset symptom

Zhonggang Wang,
Haiyan Cao,
Yuying Cao
et al.

Abstract: BackgroundIn recent years, studies on the clinical features and cognitive impairment of patients with different first-episode types of bipolar disorder have received increasing attention. The patients with bipolar disorder may present with different symptoms at first onset. The aim of this study is to assess the cognitive functions of a patient’s index episode of bipolar disorder, depression or mania, on risk factors of effecting on cognitive functions.MethodOne hundred sixty eight patients with bipolar disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…In addition, the review also addresses hyperactivityimpulsivity symptoms, emotion regulation, and the combined improvement of executive functions through multiple mini-games. It should be emphasized that improvements in executive functioning may be influenced by a variety of factors and therefore may result in a lack of observed improvements [67 ]. Improvements in working memory can be more intuitively reflected in scores on games, and inhibitory control-related abilities are improved to some extent primarily by completing impulse-suppressing game challenges.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the review also addresses hyperactivityimpulsivity symptoms, emotion regulation, and the combined improvement of executive functions through multiple mini-games. It should be emphasized that improvements in executive functioning may be influenced by a variety of factors and therefore may result in a lack of observed improvements [67 ]. Improvements in working memory can be more intuitively reflected in scores on games, and inhibitory control-related abilities are improved to some extent primarily by completing impulse-suppressing game challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of cognitive impairment in BD patients with different OP is less well-characterized. In a recent study, patients with OP-D showed the worst cognitive profile in measures of sustained attention, short-term and working memory, and cognitive flexibility [ 119 ]. These findings are in line with the pattern of differences observed in our study ( Figure 3 ), highlighting greater differences in ACC metabolites in OP-D vs. HC compared to OP-M vs. HC.…”
Section: Discussionmentioning
confidence: 99%